2014
DOI: 10.1007/s12041-014-0454-0
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and association mapping studies for important agronomic traits in soybean

Abstract: The present study was carried out with a set of 96 diverse soybean genotypes with the objectives of analysing the population structure and to identify molecular markers associated with important agronomic traits. Large phenotypic variability was observed for the agronomic traits under study indicating suitability of the genotypes for association studies. The maximum values for plant height, pods per plant, seeds per pod, 100-seed weight and seed yield per plant were approximately two and half to three times mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Indeed, putative QTLs have been detected for Single-Photon Avalanche Diode (SPAD) value, chlorophyll content, stomatal conductance, sink size, source strength, carbon isotope discrimination, and carbohydrate translocation ( Ulloa et al, 2000 ; Teng et al, 2004 ; Takai et al, 2010 , 2013 ). Potential QTLs have been revealed also for net CO 2 assimilation rate (A n ) in rice ( Ishimaru et al, 2001 ; Price et al, 2002 ; Zhao et al, 2011 ; Hirotsu et al, 2017 ; Ye et al, 2017 ; Adachi et al, 2019 ), barley ( Teulat et al, 2002 ; Cantalapiedra et al, 2015 ; Liu et al, 2017 ; Du et al, 2019 ), maize ( Fracheboud et al, 2002 ), soybean ( Jun et al, 2014 ; Lv et al, 2018 ; Liu D. et al, 2019 ), cucumber ( Zhang et al, 2004 ), and legumes ( Muchero et al, 2009 ; Kumar et al, 2014 ; Li F. et al, 2015 ). In the case of rice, several loci enhancing leaf A n have been detected on chromosomes 3, 4, 5, 6, 8, 9, and 11 ( Adachi et al, 2011 ; Gu et al, 2012 ).…”
Section: “-Omics” Analyses To Identify Novel Targets and Network Undmentioning
confidence: 99%
“…Indeed, putative QTLs have been detected for Single-Photon Avalanche Diode (SPAD) value, chlorophyll content, stomatal conductance, sink size, source strength, carbon isotope discrimination, and carbohydrate translocation ( Ulloa et al, 2000 ; Teng et al, 2004 ; Takai et al, 2010 , 2013 ). Potential QTLs have been revealed also for net CO 2 assimilation rate (A n ) in rice ( Ishimaru et al, 2001 ; Price et al, 2002 ; Zhao et al, 2011 ; Hirotsu et al, 2017 ; Ye et al, 2017 ; Adachi et al, 2019 ), barley ( Teulat et al, 2002 ; Cantalapiedra et al, 2015 ; Liu et al, 2017 ; Du et al, 2019 ), maize ( Fracheboud et al, 2002 ), soybean ( Jun et al, 2014 ; Lv et al, 2018 ; Liu D. et al, 2019 ), cucumber ( Zhang et al, 2004 ), and legumes ( Muchero et al, 2009 ; Kumar et al, 2014 ; Li F. et al, 2015 ). In the case of rice, several loci enhancing leaf A n have been detected on chromosomes 3, 4, 5, 6, 8, 9, and 11 ( Adachi et al, 2011 ; Gu et al, 2012 ).…”
Section: “-Omics” Analyses To Identify Novel Targets and Network Undmentioning
confidence: 99%
“…Pritchard et al (2000) suggested that population structure is difficult to detect using visible traits however; it may be easily detectable with molecular characters. Recently, population structure has been studied by many researchers in foxtail millet (Gupta et al 2014;Vetriventhan et al 2014;Ali et al 2016), broomcorn millet (Liu et al 2016), finger millet (Ramakrishnan et al 2016), sorghum (Kondombo et al 2016), Solanum pimpinellifolium (Rao et al 2012) and soybean (Kumar et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the added-advantages of QTL and association mapping in quantitative dissection of complex traits, a number of genes underlying QTLs associated with plant height that rely on these approaches, have been identified in crop plants, including legumes39404142434445464748495051525354. Similar major efforts have been made in the past few years towards molecular mapping of low-resolution QTLs governing plant height on multiple intra- as well as inter-specific genetic linkage maps of chickpea629343755565758.…”
mentioning
confidence: 99%